Prevalence of Self Medication in Pregnancy in Secondary and Tertiary Care Hospitals of Pakistan and Factors Contributing Towards this Malpractice - Maryam Ahmer; Rimsha Iqbal; Ayesha Akram; Habibah Ishaq Hashmi; Naila Abrar; Fehmida Shaheen; Muhammad Munir Ahmad Khan (Proceedings, 2024)
Introduction: Self-medication during pregnancy is of special concern as it can lead to serious maternal and fetal adverse effects. By controlling the factors responsible for this practice, we can promote safer health practices during this critical period of a woman’s life.